Kinetics of lithium peroxide oxidation by redox mediators and consequences for the lithium–oxygen cell - Chen, Yuhui; Gao, Xiangwen; Johnson, Lee R.; Bruce, Peter G. (Nature Publishing Group, 2018)
Lithium–oxygen cells in which lithium peroxide forms in solution rather than on the electrode surface, can sustain relatively high cycling rates but require redox mediators to charge. The mediators are oxidised at the electrode surface and then oxidise lithium peroxide stored in the cathode. The kinetics of lithium peroxide oxidation has received almost no attention and yet is crucial for operation of the lithium–oxygen cell. It is essential that the molecules oxidise lithium peroxide sufficiently rapidly to sustain fast charging. Here we investigate the kinetics of lithium peroxide oxidation by several different classes of redox mediators. We show that the reaction is not a simple outer–sphere electron transfer and that the steric structure of the mediator molecule plays an important role. The fastest mediator studied here could sustain charging current of up to 1.9 A cm–2, based on a model for a porous electrode described here. Lithium-oxygen cells in which the cathode reaction of lithium peroxide formation takes place in solution rather than on the electrode surface, can sustain relatively high cycling rates but require redox mediators to oxidise it. The mediators are oxidised at the electrode surface and then oxidise lithium peroxide particles in the pores of the cathode that are disconnected from the surface. The kinetics of lithium peroxide oxidation has received almost no attention and yet is crucial for operation of the lithium-oxygen cell. While molecules with fast electron transfer at the electrode surface are common, it is also essential that the molecules oxidise lithium peroxide sufficiently rapidly to sustain relatively fast charging. Here we investigate the kinetics of lithium peroxide oxidation by several classes of redox mediators, with varying electrochemical and structural properties (amines, nitroxy and thiol compounds). The rates range from 0.025 to 7.9 x10—3 cm s—1 with the nitroxy compounds exhibiting the highest rates. We show that the reaction is not a simple outer sphere electron transfer and that the nature of the mediator molecule plays an important role for example the steric hindrance around the active redox centre of the mediator. The fastest mediator studied here could sustain an areal current density on charging of up to 1.9 A cm—2, based on a model for a porous electrode described in the paper.